The comparison between trichloroacetic acid 50% and CO 2 laser in the treatment of cutaneous leishmaniasis scar - Mohammad Ali Nilforoushzadeh; Fariba Jaffary; Nazli Ansari; Shahram Moradi; Amir Hossein Siadat (Wolters Kluwer Medknow Publications, 2011)
Background: The scars of the cutaneous leishmaniasis and psychological problems of this disease need different interventions for its correction. Aim: Our objective in this study was to compare the efficacy of 50% trichloroacetic acid (TCA) solution and CO 2 laser for treatment of the atrophic scars due to leishmaniasis. Materials and Methods: This was a randomized clinical trial performed in 92 patients. Patients were randomized into two groups: the first group was treated with 50% TCA solution, once monthly and for a maximum of 5 months, and the second group was treated with CO 2 laser which was performed for only one time. Patients were followed-up at 3 and 6 months after starting the treatment. The improvement of scar was graded by a 6-point scale using digital camera and the collected data were analyzed using SPSS software. Results: In this study, 74 females and 18 males were enrolled. The improvement of scar was 48.13% in the TCA group and 44.87% in the CO 2 laser group. This difference was not statically significant (P = 0.55). There was also no significant difference regarding side effects between these two groups. Conclusion: The results of our study showed that efficacy of focal with 50% TCA solution is compared with CO 2 laser in treatment of leishmaniasis scar. Because of the low cost and simple application of TCA solution in comparison with CO 2 laser, we suggest use of this treatment for correction of leishmaniasis scar or the atrophic scars.